Factors influencing the International Church of Christ's decision not to require formal theological training for its Ministers from 1979-2002 - Lappeman, James R (Department of Religious Studies, 2014)
This thesis seeks to investigate why the International Church of Christ (ICoC) schism adopted a very different ministerial training approach to the one long supported by its parent church, the mainline Church of Christ (CoC). I explore how the ICoC (Formerly called the 'Boston Movement') became an independent Christian movement and identify specific reasons for the ICoC's departure from the CoC's expectation that church ministers receive an academic qualification in theology. The conclusions for this research were drawn from four sources. First, I analysed the socio-historical influences on the ICoC's philosophy of training ministers. Second, I drew from Max Weber's theory of ?charisma and routinization? to provide a theoretical understanding of how the ICoC's philosophy of education was partially an issue of authority. Third, I examined the literature directly relevant to the ICoC's training choices. Finally, I conducted a series of interviews with prominent members of the ICoC who gave their personal retelling of the early Boston Movement and why, from their perspective, the Movement adopted its methods of training. I argue that although a simple rationale was given at the time, at least eight sociohistorical factors influenced the ICoC's pendulum swing towards an almost exclusively practical approach to ministerial formation. These influences were interlinked with a high degree of corroboration between them. The influences were: - The Boston Movement's schismatic conflict with the CoC. - Kip McKean's personal experience of formal theological training. - The CoC colleges' perceived loss of training credibility. - Kip McKean's authority within the Boston Movement - The Boston Movement's narrow definition of a 'trained church minister'. - The Boston Movement's model of church replication and multiplication. - The Boston Movement's allocation of resources towards missions. - A foundation of ministers who already had a formal theological education. The thesis closes with a reflection on the findings and the ICoC's transition into its second generation of leadership.